Acellular Pertussis Vaccines Induce Anti-pertactin Bactericidal Antibodies Which Drives the Emergence of Pertactin-Negative Strains - Lesne, Elodie; Cavell, Breeze E.; Freire-Martin, Irene; Persaud, Ruby; Alexander, Frances; Taylor, Stephen; Matheson, Mary; van Els, Cécile A. C. M.; Gorringe, Andrew (Frontiers in Microbiology, 2020)
Despite high vaccination coverage, Bordetella pertussis the causative agent of whooping cough is still a health concern worldwide. A resurgence of pertussis cases has been reported, particularly in countries using acellular vaccines with waning immunity and pathogen adaptation thought to be responsible. A better understanding of protective immune responses is needed for the development of improved vaccines. In our study, B. pertussis strain B1917 variants presenting a single gene deletion were generated to analyze the role of vaccine components or candidate vaccine antigens as targets for bactericidal antibodies generated after acellular vaccination or natural infection. Our results show that acellular vaccination generates bactericidal antibodies that are only directed against pertactin. Serum bactericidal assay performed with convalescent samples show that disease induces bactericidal antibodies against Prn but against other antigen(s) as well. Four candidate vaccine antigens (CyaA, Vag8, BrkA, and TcfA) have been studied but were not targets for complement-mediated bactericidal antibodies after natural infection. We confirm that Vag8 and BrkA are involved in complement resistance and would be targeted by blocking antibodies. Our study suggests that the emergence and the widespread circulation of Prn-deficient strains is driven by acellular vaccination and the generation of bactericidal antibodies targeting Prn.